Emergency medicine procedures - Simon, Robert R. (Robert Rutha) (McGraw-Hill Education/Medical, 2013)
Helps you master the clinical and technical skills required to perform the full range of procedures in an emergency or acute care setting. This title includes techniques that expand your understanding of emergency medicine procedures and - your ability to deliver positive patient outcomes.